(untitled) (Scientific journal of the Fergana State University, 2023)
The article describes the amount of microelements in the meadow-oasis soils and the plant Indigofera tinctoria L., formed in the climatic conditions of the Fergana region. The amount of trace elements was compared with the lithosphere and soil chlorite. The amounts of Zn, Cr, Ni, Co, As and Mo were determined in the composition of basma (Indigofera tinctoria L.) grown in meadow-oasis soil conditions.